PENGARUH KUALITAS PELAYANAN JASA TERHADAP KEPUASAN KONSUMEN (Survei pada Rumah Sakit Umum Daerah Kabupaten Sragen) - Ernawati, Suprapto & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2009)
ABSTRACT This research aim to to know the influence which signifikan among/between : (1) Tangibles to consumer satisfaction, (2) responsiveness to consumer satisfaction, (3) assurance to consumer satisfaction (4) empathy to consumer satisfaction Â Public Hospital Area Sub-Province Sragen. Its Population is service user public hospital health service area Sub-Province Sragen. Sampel taken at random counted 70 people. Technique analyse to use the doubled linear regresi with the classic assumption test. Conclusion result research : (1) Hypothesis expressing variable tangibles have an effect on to consumer satisfaction public hospital area tested its truth, (2) Hypothesis expressing variable responsiveness have an effect on to consumer satisfaction public hospital area not tested truth. (3) Hypothesis expressing variable assurance have an effect on to consumer satisfaction public hospital area not tested its truth (4) Hypothesis expressing Â variable empathyberpengaruh to consumer satisfaction public hospital area tested its truth (5) Hipotesis expressing fourth free variable by simultan have an effect on to consumer satisfaction tested its truth. Keywords : Tangibles, responsiveness, assurance, empathy